Streak observation of dc pre-breakdown phenomenon in silicone oil/low density polyethylene (LDPE) with different viscosities - Amir Izzani, Mohamed; Ozaki, Ryotaro; Kadowaki, Kazunori (School of Electrical Engineering and Informatics, 2013)
We observe streak images of dc pre-breakdown in silicone-oil (10 cSt, 100 cSt and 10000 cSt)/low density polyethylene (30 μm in thickness) composite insulation under needle/sphere electrode by using the 20 meter long image guide scope and a streak camera. In the case of composite insulation with 10 cSt of silicone-oil, breakdown light propagates from the needle side under both voltage polarity. However, in the 10000 cSt case, breakdown light propagates from the film side under the negative voltage polarity. The mechanism of these transient phenomena are discussed in this paper.